La représentation syndicale: visage juridique actuel et futur - Weiss, Dimitri (Relations industrielles / Industrial Relations, 2000)
The article reviews the book, "La représentation syndicale: visage juridique actuel et futur," by Gregor Murray and Pierre Verge.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; Labor relations; Laws & regulations; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z